Pemeriksaan Real Time-Polymerase Chain Reaction (RT-PCR) pada Granuloma Well Organized dan Poorly Organized Limfadenitis Tuberkulosis - Dianti Lestari; Birgitta M Dewayani; Abdul Hadi Hassan; Bethy S Hernowo (Majalah Patologi Indonesia, 2016)
Introduction Tuberculous lymphadenitis (TBL) was the most common form of extrapulmonary tuberculosis. The diagnose of TBL was based on the tubercle formation that consist of granuloma and caseous necrosis. There were 2 type of granuloma, well organized (WOG) and poorly organized granuloma (POG). Well organized granuloma were characterized by varying amount of eosinophilic necrosis surrounded by granuloma composed of mature epithelioid macrophages, mainly Langhans type giant cells and a mantle of lymphocytes and fibrous tissues. Poorly organized granuloma were characterized by central area of sparse coarse necrosis with nuclear debris and often polymorphonuclear granulocytes, the granuloma had an ill-defined mantle with mixed cells composed of macrophages, lymphocytes and plasma cells, only few giant cells were seen and there was little or no fibrosis. Inflamatory granuloma also can be found in non TBL, especially POG. The purpose of this study was to find out the etiology of WOG and POG based on the RT-PCR result. Methods This study used 30 formalin-fixed paraffin-embedded tissue blocks from patients who were histopathologically diagnosed as TBL with hematoxillin eosin (HE) staining, consist of 15 samples WOG and 15 samples POG. This study performed RT-PCR to all cases in order to find out the etiology of GWO and GPO and to know if there will be any differences in RT-PCR result between WOG and POG. Results Of the 15 WOG cases, 10 (67%) cases were RT-PCR positive and 5 (33%) cases were RT-PCR negative, whereas 15 cases POG consist of 8 (53%) cases were RT-PCR positive and 7 (47%) cases were RT-PCR negative. Both of cases WOG and POG was analyzed, according to the statistical analysis had found that there were no differences RT-PCR result between WOG and POG significantly (p>0.05). Conclusion There were no differences in RT-PCR result between histopathologic feature of WOG and POG. Key words : Poorly organized granuloma, RT-PCR, tuberculosis lymphadenitis, well organized granuloma.